PLACE ATTACHMENT BASED URBAN REFORM AS TOURISM POTENTIAL OF KAMPONG SEMUT - Putu Bulan Ratna Anggraeni; Fery Asta Wibowo (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2019)
Tourism activities can never be separated from the history of a city and the influence of the development of the city itself. Aspects of tourism are very dependent on culture and public understanding of a tourist attraction in a city. Kampong Semut is one of the historical relics of the city of Surabaya which has the potential to become a tourist facility. The potential is due to the fact that Kampong Semut has a potential in the form of community attachment to the location. The community's attachment to a Kampong Semut, changing the form and function of the village itself from a large-scale activity center to an urban village that is not conserved. The purpose of this study is to understand more deeply the place attachments that exist in Kampong Semut and see what potential can be developed back into a tourism potential to be able to return the Kampong Semut to its former glory. This study uses an urban analysis method to see the shape of the city and the layers of the city in Kampong Semut to see the changes brought by the people in Kampong Semut to the place attachments.